Symbolic interaction and new social media - Johns, Mark D.; Chen, Shing-Ling; Terlip, Laura A. (Studies in symbolic interaction, 2014)
The new social media build on and further complicate all of the issues and processes of symbolic interaction. This volume builds on and expands the existing symbolic interactionist perspective to include the study of social interaction made possible by the use of new social media. This special issue demonstrates the interface between willful social interaction and structured technological featureshow social media are defined by social interactions, as well as how social interactions are dictated by the use of social media.